The Payout Phase of Pension Systems : A Comparison of Five Countries - Rocha, Roberto; Vittas, Dimitri; Rudolph, Heinz P. (2012)
This paper provides a comparative summary of the payout phase of pension systems in five countries -- Australia, Chile, Denmark, Sweden, and Switzerland. All five countries have large pension systems with mandatory or quasi-mandatory retirement savings schemes. But they exhibit important differences in the structure and role of different pillars, regulation of payout options, level of annuitization, market structure, capital regulations, risk management, and use of risk sharing arrangements. The paper summarizes the experience of these countries and highlights the lessons they offer to other countries.